Gather the Women - Fisher, Liz; Browne, Sonya; Kohutiak, Barbara (Groupwork, 2014)
Gather the Women (GTW) is a program for women with limited financial resources that includes groupwork and is designed to guide participants toward economic advancement and personal growth. The participants were interviewed to understand more about their perspectives of the group and how it has affected them. This article presents an overview of the program, a description of each woman in her own words and identifies several themes regarding reasons for joining the group, group norms, relationships, future outlook and program factors. Results indicate that the group has improved their trust in other women, self-confidence, self-esteem and views of the future. These outcomes may contribute to an overall sense of empowerment and are necessary for working on their goals for economic advancement.